Implementation of Mobile Smart Key System using the NFC Function of the Smartphone - Geon Pak, Ju; Ram Lee, Bo; Suk Lee, Myung (International Journal of Engineering and Technology, 2018)
As the numbers of traveler increases and BYOD culture spreads, this study developed a smart key system using NFC of smart phone that allows people to use their smart phones to easily make room reservations and enter their rooms without separate keys. This system attempts to resolve difficulties experienced while managing and utilizing accommodations from a distance, difficulties experienced when users lose keys or forget their password and in communication between users and managers. The test results in the actual locker management, it is very useful to utilize of the locker administration in the various place, as well as useful accommodation. The implemented smart key system has the benefit to control the Doorlock without a secret number.Â Â